2013
DOI: 10.1371/journal.pone.0061366
|View full text |Cite
|
Sign up to set email alerts
|

Microvesicles Derived from Human Umbilical Cord Wharton’s Jelly Mesenchymal Stem Cells Attenuate Bladder Tumor Cell Growth In Vitro and In Vivo

Abstract: Several studies suggest that mesenchymal stem cells (MSCs) possess antitumor properties; however, the exact mechanisms remain unclear. Recently, microvesicles (MVs) are considered as a novel avenue intercellular communication, which may be a mediator in MSCs-related antitumor effect. In the present study, we evaluated whether MVs derived from human umbilical cord Wharton’s jelly mesenchymal stem cells (hWJMSCs) may inhibit bladder tumor T24 cells growth using cell culture and the BALB/c nu/nu mice xenograft mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
171
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(178 citation statements)
references
References 58 publications
6
171
1
Order By: Relevance
“…Consistent with the present results, Wu et al (18) demonstrated that microvesicles from human UCMSCs could inhibit the functions of T24 bladder cancer cells. The study also demonstrated that this proliferation suppression was mediated by cell cycle arrest and the induction of apoptosis was mediated by increased expression of caspase 3.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the present results, Wu et al (18) demonstrated that microvesicles from human UCMSCs could inhibit the functions of T24 bladder cancer cells. The study also demonstrated that this proliferation suppression was mediated by cell cycle arrest and the induction of apoptosis was mediated by increased expression of caspase 3.…”
Section: Discussionsupporting
confidence: 92%
“…Human foreskin fibroblasts (HFFs) were also obtained from a commercial source (Shanghai Institutes for Biological Sciences) and cultured in RPMI-1640 (Gibco) supplemented with 10% FBS. EVs extraction and characterisation EVs were obtained from hWJMSC and HFF supernatants as previously described [20][21][22]. In brief, cells were cultured in FBS-deprived medium and supplemented with 0.5% bovine serum albumin (BSA, SigmaAldrich, USA) overnight.…”
Section: Cell Culturementioning
confidence: 99%
“…Wharton's jelly MSC-EVs can attenuate the growth of T24 bladder tumor cells in vitro and in vivo by arresting the cell cycle in G 0 /G 1 phase and inducing cell death by apoptosis. Analysis of Akt/ p-Akt by Western blotting revealed that the mechanism involved in the suppression of T24 proliferation is mediated by a reduction in phosphorylation but not in the total expression level of Akt (106). EVs derived from adipose MSCs also had tumor inhibiting effects.…”
Section: Anti-tumorigenic Role Of Msc-derived Vesiclesmentioning
confidence: 99%